Technostress in Cybersecurity: Evaluating Its Effects on Professional Performance and Organisational Security - Pillai, Jayan Kopparethu Gopinadhan (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
Cybersecurity professionals operate in a high-stakes environment, constantly adapting to evolving threats and managing complex technologies. This intense workload often leads to technostress—the mental and emotional strain caused by excessive technological demands. This study explores how technostress affects cybersecurity professionals, particularly its impact on job performance, decision-making, and organisational security. Through surveys and interviews, the research highlights how stress leads to slower responses, increased errors, and a higher risk of security breaches. Many professionals experience burnout, and with cybersecurity talent in short supply, organisations face additional challenges in maintaining strong security defences. The findings emphasise the urgent need for companies to address technostress by implementing work-life balance initiatives, automation tools, and stress management programs. By doing so, they can create a healthier work environment while also strengthening their overall security posture.